Quizizz Aided Circ Type Cooperative Learning Model To Improve Problem Solving - Parmin Lumban Toruan; Rahmawati Rahmawati (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
This study aims to see the improvement of students' mathematical problem solving abilities using a learning model using cooperative integrated reading and composition type Circ (cooperative integrated reading and composition) learning assisted by Quizizz to improve problem solving . This model is learning by delivering teaching materials that he guardians by forming groups, provide discourse according to the topic of learning, students work together to read each other and find the main ideas contained in the discourse then provide responses to the discourse written on paper sheetss, Students present / read out the results of group discussions, the teacher provides reinforcement and makes conclusions together. The research subject was the research subject was the student of class X MAN 1 Palembang in the academic year 2020-2021. This method is Quasi-Experimental. There are two types of research data. Quantitative and qualitative data. Data were analyzed using descriptive analysis and obtained calculations. It was found that students who received learning with the Circ type cooperative learning (cooperative integrated reading and composition) assisted by Quizizz showed a post test score that was greater than conventional learning